Long working hours at midlife and arterial stiffness at older age in a 24-year prospective cohort - Carolina Braga Sisti; Mahée Gilbert-Ouimet; Mathilde Lavigne-Robichaud; Chantal Brisson; Alain Milot; Xavier Trudel (BMC Public Health)
Abstract Backgrounds This study aims to examine whether long working hours, repeatedly assessed at midlife, is associated with higher arterial stiffness at older age in a 24-year prospective study of white-collar workers in Quebec City, Canada. Methods This study relied on a prospective cohort, initiated in 1991–1993 (T1) with two follow-ups after 8 years (T2, 1999–2001) and 24 years (T3, 2015–2018). Participants (N = 1,629, 51.3% women, mean age 37 ± 6.4 at T1) were randomly selected for arterial stiffness measurement at T3 using carotid-femoral pulse wave velocity (PWV). Long working hours (> 40 h/week) were assessed at T1 and T2. Mean differences in PWV were estimated using generalized linear models, accounting for sociodemographic factors, lifestyle-related risk factors, clinical factors and psychosocial stressors at work. Results Among participants who remained actively employed over the study period (age range: 21–59 at T1), long working hours at T1 were associated with a + 0.54 m/s (95% CI: 0.05; 1.02) increase in PWV, while repeated exposure at T1 and T2 was associated with a + 1.50 m/s (95% CI: 0.78; 2.21) increase. No association was observed among participants who retired between T2 and T3. Conclusion The present study suggests that exposure to long working hours during midlife is associated with higher arterial stiffness, among aging workers. Workplace preventive strategies reducing long working hours may be effective to mitigate long-term arterial stiffening.